Physics based analytical model for surface potential and subthreshold current of cylindrical Schottky Barrier gate all around MOSFET with high-k gate stack. (February 2016) - Kumar, Manoj; Haldar, Subhasis; Gupta, Mridula; Gupta, R.S.
Abstract: A physics-based analytical model for Schottky Barrier (SB) Cylindrical Gate All Around (CGAA) MOSFET with high- k dielectric is presented with Evanescent Mode Analysis (EMA). The electrostatic potential is obtained using the Superposition method. An exact expression for threshold voltage and subthreshold slope is also obtained. The proposed model also includes the effect of Barrier height lowering at metal semiconductor interface along with the effect of high-k (HfO2 ) gate stack. Diffusion current and tunneling currents are combined to evaluate the total subthreshold current. The analytical results so obtained are compared with simulated data and they are in good agreement. The proposed model of SB-CGAA device with high-k dielectric is very useful for the design and optimization for high current and improved performance. Highlights: New physics base analytical drain current model for SB-CGAA MOSFET. High-k gate stack architecture of SB-CGAA MOSFET. Lightly doped channel (NA = 1 × 10 16 cm −3 ). Low power and high speed. Improved subthreshold slope behaviour.